Negative Emission Technologies and Climate Cooperation - Michela Boldrini; Valentina Bosetti; Salvatore Nunnari (Center for Economic Studies and ifo Institute (CESifo), 2024)
Negative Emissions Technologies (NETs) — a range of methods to remove carbon dioxide from the atmosphere— are a crucial innovation in meeting temperature targets set by international climate agreements. However, mechanisms which undo the adverse consequences of short-sighted actions (as NETs) can fuel substitution effects and crowd out virtuous behaviors (e.g., mitigation efforts). For this reason, the impact of NETs on environmental preservation is an open question among scientists and policy-makers. We model this problem through a novel restorable common-pool resource game and use a laboratory experiment to exogenously manipulate key features of NETs and assess their consequences. We show that crowding out only emerges when NETs are surely available and cheap. The availability of NETs does not allow experimental communities to either conserve the common resource for longer or accrue higher earnings and makes the earnings distribution more unequal.
Keywords: C92; H41; Q55; 330; climate crisis; environmental sustainability; carbon dioxide removal; common-pool resource; free-rider problem; laboratory experiment